If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + g = 2g Solving 6 + g = 2g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-2g' to each side of the equation. 6 + g + -2g = 2g + -2g Combine like terms: g + -2g = -1g 6 + -1g = 2g + -2g Combine like terms: 2g + -2g = 0 6 + -1g = 0 Add '-6' to each side of the equation. 6 + -6 + -1g = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -1g = 0 + -6 -1g = 0 + -6 Combine like terms: 0 + -6 = -6 -1g = -6 Divide each side by '-1'. g = 6 Simplifying g = 6
| -8+w=2w | | 50625a+36a+a= | | 3v^2-8v-35=0 | | 2x+3-5=20 | | 12x+y=20 | | 4x^2+36x-84=0 | | 10=u-4 | | v-5=9 | | 15a+6a+a= | | 11=8+y | | B=xt+xfort | | -1=7+4u | | -3(2-z)-8z=15 | | N-1=8n-8 | | 4*a+4*4*b= | | 2v-3=-13 | | -22=4w+2 | | x+1/7=29/7 | | 8+5w=-27 | | 4y-1+y+48=5y+50-3y | | 2u-5=-1 | | 2-4n=30 | | -4(x-5)-16x=10 | | t^4-13t^2+42=0 | | 185x+.25=.275(7) | | -27+(-14)= | | 5t-2=3 | | 2(2x-2)=10 | | y=2x^2+4x-4 | | 2t^2+11t-40=0 | | x^2+y^2+22x+12y+93=0 | | (x-2)(2+x)=(x-3)-1 |